CONCEPTUAL FOUNDATIONS FOR IMPROVING THE PROFESSIONAL COMMUNICATION SKILLS OF STUDENTS OF TRANSLATION FACULTIES - Abduganieva Djamilya Rustamovna (Western European Studies, 2023)
This article investigates the development of communication skills among students of translation faculties, emphasizing linguistic proficiency, cultural competence, and the integration of technology. The study draws on theoretical frameworks, existing models, and empirical research to inform the design and implementation of an intervention program. Results indicate significant improvements in participants' self-perceived communication proficiency, showcasing the effectiveness of real-world simulation exercises and technology-based activities. The role of technology in skill acquisition and successful strategies, such as virtual collaboration tools, is explored. Comparative analysis with existing literature reveals the relevance of the intervention, contributing practical insights for educators. The implications for translation education underscore the need for a holistic approach, integrating communication skills into curricula to prepare students for the digital demands of the profession
Keywords: Communication skills; translation education; linguistic proficiency